Local government shift and national housing program: Spatial repercussions on urban growth - Menzori, Ivan Damasco; de Sousa, Isabel Cristina Nunes [UNESP]; Gonçalves, Luciana Márcia (Elsevier, 2023)
This paper contributes to understanding the territorial politics of urban growth, especially concerning the strategies and means of controlling urban expansion (transformation of natural or rural land into urban, built-up areas). We analysed the urban growth/expansion processes resulting from three consecutive periods of master plan implementation practices in a medium-sized Brazilian city (Araraquara). The goal was to quantitatively assess whether a national market-oriented housing program (MCMV) could be accountable for disparities in spatial outcomes of physical growth associated with different territorial governance arrangements during contrasting local government mandates. Although the MCMV program introduced extensive peri-urban expansion, especially towards headwater preservation areas that nowadays juxtapose social and environmental vulnerabilities in Araraquara, it was not solely responsible for the discernible spatial trends observed after 2009. These results offer insights into how changes in territorial governance arrangements can affect master plan implementation practices.
Keywords: Local government; Master plans implementation; MCMV; Social housing; Urban growth